Potensi dan tantangan kecerdasan buatan sebagai asisten belajar mahasiswa FKIP dalam menyelesaikan tugas akademik - Wardani, Happy Kusuma; Mazidah, Eva Nur; Hidayah, Bariqotul (CV. Kurnia Grup, 2024)
The aim of this research is to find out how students in Mathematics and English Language Education programs at Faculty for Teacher Training and Education of Qomaruddin University utilize Artificial Intelligence (AI) as learning assitant to complete their academic assignments. A qualitative method was used to explore students' perspectives on AI, their favorite AI tools, as well as the potentials and challenges of AI in their academic performances. The results of this research indicate that majority students utilized AI not only to accomplish their academic assignments but also to improve their learning outcomes. Furthermore, ChatGPT is the most popular AI tool utilized by the students. This research also emphasizes the need for responsible AI utilization to maximize its benefits.